Transceiver and system design for digital communications - Bullock, Scott R. (SciTech Publishing, 2014)
This is the fourth edition of this successful professional reference book on transceiver design, the device that both sends and receives signals, and its place within the wireless communication system. It gives engineers and others a good intuitive understanding of wireless systems and spread spectrum. New topics covered include cognitive radio, systems, networks, and commercial communications. In addition, many items have been extensively updated to improve the flow of the book and enhance comprehension.